Implementation Of Solar Cells For Energy Sources In Hydroponic Automation Systems - Munawarah Munawarah; Tholib Hariono; MasHudi Ainun Gofar (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The hydroponic plant management automation system uses electronic devices that require electrical energy for these devices to work. The supply of electrical energy will be a problem in a power outage or the location of plants far from the power source. In addition, the continuous use of electricity will also increase the operational costs of plant maintenance. This research implements solar cells for electric power generation to activate sensor devices in hydroponic plant automation systems. The main device is a 60-watt solar panel with 5A battery storage to activate sensors in the hydroponic automation system. The study results can be concluded that this equipment can help source energy in hydroponic automation systems. The battery charging process takes an average of 100 minutes (without using a load) and takes an average of 155 minutes (with a load).